Innovation of contextual-based module on thematic learning in elementary schools - Eko Eko; Pardimin Pardimin; Ana Fitrotun Nisa (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
This study aims to develop a contextual-based module on thematic learning in elementary schools. This research uses research and development (R&D) methods. This study uses a modified 4D model development research method, namely define, design, development, and disseminate. The data collection instrument used is a questionnaire or questionnaire given to material expert validators and media expert validators to see the validity of the product and student response questionnaires. The research involved 11 students in the trial. The results of this study are a product in the form of a contextual-based module in the thematic learning of class VI SD with the results of a feasibility assessment from a material expert after validating an average score of 3.45 with a percentage of 86.31% with valid criteria and from media, experts obtained an average score of 3.45. the average score is 3.60 with a percentage of 90.02% with very valid criteria. The results of the practicality assessment by students in small group trials with 11 students as subjects obtained an average score of 19.94 with a percentage of 82.82% with appropriate criteria; the resulting module product has met the valid and feasible criteria. Therefore, this module is feasible to use.